Blockchain-Based Secure e-KYC Solution for Banking System - Tabassum, Zoya; Arsheen, Sobiya; Ahmad, Khaleel; Ozdemir, Gulcihan (Proceedings (International Confernce on Computational Intelligence and Communication Networks), 2024)
Blockchain technology offers a secured, digital, decentralized, ever-growing ledger that keeps records tamper-proof. The distributed ledger means that, even if one node is attacked or hacked, data may be accessed from other nodes, making the system more resistant to attacks and ensuring data availability. The hash function is used to strengthen the data integrity. E-KYC stands for electronic Know Your Customer, a way to verify a customer's identity. The banks frequently require the customer's identity documents for verification. Therefore, they spend an unwanted cost, effort, and abundant time during the KYC process. Sometimes, the information stored locally can be misleading. With unique features, blockchain-enabled e-KYC systems can protect sensitive data, reduce data breach risks, and ensure the integrity and confidentiality of e-KYC procedures. With its distributed ledger, blockchain technology stores e-KYC data across nodes and cryptographic techniques and can effectively increase e-KYC safety. Decentralization and immutability make blockchain technology a strong foundation for securing sensitive customer data. Strong authentication and public key cryptographic methods to protect e-KYC data.